2009
DOI: 10.1016/j.jvs.2009.01.014
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative outcomes in intimal aortic angiosarcoma: A case report and review of the literature

Abstract: Intimal angiosarcoma is a most unexpected cause of aortic occlusion. We present the case of a 74-year-old woman with intimal angiosarcoma that manifested with the triad of congestive heart failure, acute renal failure, and abdominal angina. A review of the literature and discussion of postoperative outcomes follows.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 9 publications
0
11
0
Order By: Relevance
“…5 There is also evidence that an erythrocyte sedimentation rate Ͼ100 should increase the suspicion of an underlying angiosarcoma. 13 Recent reports suggest that magnetic resonance angiography with gadolinium is the most sensitive imaging method for diagnosing intimal sarcomas due its ability to differentiate between tumor, atheromatous lesions, and normal arterial wall on the basis of contrast enhancement of the tumor. 1,10,11 Magnetic resonance imaging provides additional benefit through its ability to assess the degree of arterial wall involvement, as well as tumor invasion into surrounding tissues.…”
Section: Discussionmentioning
confidence: 99%
“…5 There is also evidence that an erythrocyte sedimentation rate Ͼ100 should increase the suspicion of an underlying angiosarcoma. 13 Recent reports suggest that magnetic resonance angiography with gadolinium is the most sensitive imaging method for diagnosing intimal sarcomas due its ability to differentiate between tumor, atheromatous lesions, and normal arterial wall on the basis of contrast enhancement of the tumor. 1,10,11 Magnetic resonance imaging provides additional benefit through its ability to assess the degree of arterial wall involvement, as well as tumor invasion into surrounding tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Another original point in our case is that IS skin metastasis, to the best of our knowledge, never has been reported. Reported sites of IS metastases include brain, kidney, bone, duodenum, liver and lungs, but at the time of the diagnosis, our patient did not have any extra‐cutaneous metastases.…”
Section: Discussionmentioning
confidence: 65%
“…Aortic IS commonly begins with claudication, a consequence of emboli . This can delay the diagnosis that sometimes can be established only on autopsy .…”
Section: Discussionmentioning
confidence: 99%
“…Surgical radical resection is the most effective method for aortic sarcoma. Nicotera et al (13) reported a mean survival time (17.1±21.6 months) in 16 patients with en bloc resection through literature review. At first, this lesion in this study was reckoned as thrombus.…”
Section: Discussionmentioning
confidence: 99%